Endobronchial laryngeal tumor "embolus"creating respiratory difficulty during surgery: A case report - Ray Dieter (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2021)
Unusual laryngeal and tracheobronchial obstructing lesions are seen on occasion [1-3]. A patient was evaluated by his primary physician and pulmonologist due to symptoms referable to his chest including a cough and shortness of breath. Evaluation, including lexible bronchoscopy, revealed a primary carcinoma of the left upper lobe of the long.